TRENDS AND INNOVATIONS IN EMPLOYEE TRAINING AND DEVELOPMENT IN THE FACE OF MODERN CHALLENGES (Development Service Industry Management, 2024)
The article is dedicated to analyzing the main trends and innovations in the field of employee training and development in the context of modern challenges, particularly in light of technological changes, globalization, and the rapid adaptation to new working conditions. The paper examines key areas of corporate learning development, including the use of digital technologies, online courses, interactive platforms, and artificial intelligence to personalize the learning process. Special attention is paid to the importance of flexible learning methods that foster the development of skills necessary for effective work in environments characterized by continuous change. The study identifies the main innovative approaches to the development of corporate universities and academies, the role of mentorship and coaching in supporting professional growth, and the need to integrate psychological aspects into educational programs to ensure emotional resilience and employee motivation. It discusses the challenges associated with the implementation of new technologies in training processes, as well as the need to develop soft skills among employees for effective interaction in contemporary conditions. Given the relevance of the topic in light of global changes, the article offers practical recommendations for organizations on adapting training programs to new realities and introducing innovative approaches into the employee development process. The article also outlines the prospects for the development of the learning and development industry, taking into account the continuous advancement of technologies, labor market needs, and the increasing demands for professional competence in a rapidly changing world.
Keywords: innovation; learning; employee development; professional growth; human capital; corporate training